Sarapoa Republic Vs. Juana Elizabeth Guzman and others - Zapata, Iván Darío (2023)
After a transitional justice process, different guerrilla groups located in the State of Sarapoa abandoned the fight and merged to the civil life. As part of the peace talks, the government allowed political participation to former members of the guerrilla, through a political party called “Propuestas por la Paz”, which elected Aura Bonilla as Congresswoman and Elizabeth Guzmán as the mayor of the capital. Overthrowing and subsequent inability of both women, made by the state ́s General Solicitor, antagonize with the most basic standards on political rights and restricts the cornerstone of the due process of law: the double jeopardy clause. The following lawsuit approaches the problem through the case law of the Inter-American Human Rights Court, taking special care of the institutional design of the State of Sarapoa, and the establishing the international responsibility for it.